'Not at all afraid': Queer Temporality and the School Detective Story. (September 2021) - Baker, Timothy C.
Abstract : Kate Haffey has recently argued that if queer time can be seen as a turning away from narrative coherence, it suggests new possibilities for considering narrative structures more generally. Combining the narratively rigid structures of the school story and the detective novel, the four novels discussed in this article – Gladys Mitchell's Laurels are Poison (1942), Josephine Tey's Miss Pym Disposes (1946), Shirley Jackson's Hangsaman (1951), and Joan Lindsay's Picnic at Hanging Rock (1967) – disrupt conventional understandings of linear time. Depicting not only queer, or potentially queer, characters, but a queer phenomenological perspective, they challenge reader expectations with a focus on aporias and gaps, whether in terms of trauma (Jackson), the blurring of fact and fiction (Lindsay), or the prolonged delay of both crime and resolution (Tey). These novels draw attention to the insufficiency of texts to capture experience, and the inadequacy of textual authority. As such, they reveal the extent to which mid-twentieth-century women's fiction was able to challenge the genres and narrative structures with which it was most closely associated.